Exploring the Role of Mass Media in Crime Prevention and Control: A Study of Chikun Local Government Area, Kaduna State, Nigeria - Kamal Muhammad Sani; Jamilu Ibrahim Mukhtar; Mukthar Abubakar Hassan; Ahmed Haruna Danjuma (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aims to explore the role of the mass media in crime prevention and control in Chikun Local Government Area (CLGA), Kaduna State, Nigeria. Both quantitative and qualitative methods were employed to collect data from a sample of 600 respondents, with 50 respondents selected from each of the 12 political wards in CLGA using simple random sampling techniques. The data was analyzed using the Statistical Package for Social Sciences (SPSS Version 26) software. The study findings demonstrate that the majority of respondents are aware of and acknowledge the significant role played by the mass media in crime prevention and control in CLGA. The study also highlights the pivotal role of social media in reaching a wider audience in crime prevention and control efforts. Additionally, the study identifies several challenges faced by the mass media that hinder effective crime prevention and control, such as hate speech, the dissemination of false or misleading information, unfavorable communication policies, and a lack of competent media personnel. Based on these findings, the study offers recommendations to address these challenges and enhance the impact of mass media in crime prevention and control efforts.